p-Adic Markov process and the problem of the first return over balls - Casas-Sánchez, O. F.; Galeano-Peñaloza, J.; Rodríguez-Vega, J. J. (Ukrains’kyi Matematychnyi Zhurnal, 2021)
UDC 511.225, 519.217, 511.225.1, 303.532 We consider the pseudodifferential operator defined as H^αφ = F^-1[(ξ^α - p^rα)F_φ], where ξ = ({|ξ|_p, p^r})^α and study the Markov process associated to this operator. We also study the first passage time problem associated to H^α for r<0.